Activity of Averrhoa Bilimbi L Leaf Extract as Denture Cleaner Towards The Number of Colonies of Candida Albicans in Heat Cured Resin with a 30 Minutes Period - Idamawati; Rouli Natasia; Molek; Listyaning Kartiko Kinasih (Biomedical Journal of Indonesia, 2021)
Denture stomatitis is a chronic inflammatory condition of the oral mucosa that generally occurs in users of removable dentures. The cause is multifactorial but is often associated with the presence of Candida albicans. The mucosa which is covered by the denture base also reduces the function of saliva which functions as a cleanser for the oral cavity and results in food waste accumulating and microorganisms such as Candida albicans can increase in number. Candida albicans is a normal flora of the oral cavity which is an opportunistic pathogen. The starfruit plant (Averrhoa billimbi l) is a natural ingredient that can be used as an antifungal agent. The aim was to determine the ratio of the effectiveness of starfruit leaf extract (Averrhoa billimbi) between the concentrations of 12.5%, 25%, 50%, 100%, control + (Clorhexidine) and control - (Aquadest) in reducing the number of Candida albicans colonies. The test method used the dilution method, the colony count of Candida albicans using a spectrophotometer. The results of the one way ANOVA statistical test resulted in a significance value of p = 0.000 (p <0.05) which means that there is a difference in the average concentration of Candida albicans between the extract concentrations of 12.5%, 25%, 50%, 100%, control + and control. -namely 6.78 ± 0.35, 6.27 ± 0.21, 4.89 ± 0.29, 1.01 ± 0.18, 0.59 ± 0.19 and 9.13 ± 2.28 in inhibiting growth Candida albicans and this was confirmed by the Tukey HSD posthoc test. The conclusion of this study is that there is a difference between the antifungal effectiveness of starfruit leaf extract (Averrhoa billimbi) concentrations of 12.5%, 25%, 50% and 100% in inhibiting the growth of Candida albicans colonies.